2011
DOI: 10.1007/s10570-011-9497-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cellulose nanofibers from four plant cellulose fibers using a chemical-ultrasonic process

Abstract: Cellulose nanofibers (CNFs) were isolated from four kinds of plant cellulose fibers by a chemical-ultrasonic treatment. The chemical composition, morphology, crystalline behavior, and thermal properties of the nanofibers and their intermediate products were characterized and compared. The CNFs extracted from wood, bamboo, and wheat straw fibers had uniform diameters of 10-40 nm, whereas the flax fibers were not uniformly nanofibrillated because of their initially high cellulose content. The chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
211
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(232 citation statements)
references
References 58 publications
17
211
2
2
Order By: Relevance
“…In addition, the present finding was similar to several studies listed in Table 3, where the Tmax value of yielded nanocellulose obtained from various biomass sources rendered lower values than that of crude cellulose material. The Tmax values of yielded nanocellulose derived from wheat straw (Tmax = 332.2 °C) (Chen et al 2011), empty fruit bunch (Tmax = 339 °C) (Jonoobi et al 2011), and mulberry bark (Tmax = 335 °C) (Li et al 2009) are shown. Fortunately, all the cellulose nanoparticles were stable when the heating temperature was less than 280 °C.…”
Section: Morphological Study (Afm Analysis)mentioning
confidence: 99%
“…In addition, the present finding was similar to several studies listed in Table 3, where the Tmax value of yielded nanocellulose obtained from various biomass sources rendered lower values than that of crude cellulose material. The Tmax values of yielded nanocellulose derived from wheat straw (Tmax = 332.2 °C) (Chen et al 2011), empty fruit bunch (Tmax = 339 °C) (Jonoobi et al 2011), and mulberry bark (Tmax = 335 °C) (Li et al 2009) are shown. Fortunately, all the cellulose nanoparticles were stable when the heating temperature was less than 280 °C.…”
Section: Morphological Study (Afm Analysis)mentioning
confidence: 99%
“…The yield of the process was estimated by comparing the obtained amount of NCC with the cellulose percentage present in the initial residual biomass. Concerning the NCC steps in Sections 2.2.4 and 2.2.5, some experimental procedures using an integrated approach of acid hydrolysis and ultrasonic treatment are available in the literature [26][27].…”
Section: Ultrasound Treatmentmentioning
confidence: 99%
“…Besides, FTIR spectra were used to confirm the removal of lignin and hemicelluloses from various LBW samples. After strong alkaline treatment, no absorption peak was observed at 1735 cm −1 , which was attributed to the complete 3 International Journal of Polymer Science removal of hemicelluloses and/or lignin components [29]. In addition, no absorption peak attributed to the -C=C-stretching of aromatic rings of lignin was observed at 1513 cm −1 , thereby confirming that all lignin had been removed from cellulose fibres isolated from various LBW samples (Figure 1(b)) [30].…”
Section: Resultsmentioning
confidence: 80%